The equivalent area and active mass of microphone membranes - MAKAREWICZ, Rufin; KONIECZNY, Jacek (Archives of Acoustics, 1977)
The paper presents a proposed method for determining the equivalent area and active mass of microphone membranes. It is based on an energetic definition of these parameters and assumes a flat piston. It requires a knowledge of the phase distribution and also of the displacement amplitude and velocity over the whole surface of the real membrane. The methodology of measuring these quantities is the subject of a separate publication. In these considerations the effect of the wavelength, the direction of incidence and the effect of the membrane shape on the active parameters are taken into account. Indirectly, the manner of mounting the membrane at its border has also been considered.